2013
DOI: 10.1007/s10751-013-0806-9
|View full text |Cite
|
Sign up to set email alerts
|

Cold highly charged ions in a cryogenic Paul trap

Abstract: Narrow optical transitions in highly charged ions (HCIs) are of particular interest for metrology and fundamental physics, exploiting the high sensitivity of HCIs to new physics. The highest sensitivity for a changing fine structure constant ever predicted for a stable atomic system is found in Ir17 + . However, laser spectroscopy of HCIs is hindered by the large (∼ 106 K) temperatures at which they are produced and trapped. An unprecedented improvement in such laser spectroscopy can be obtained when HCIs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Recently, a combination of HCI production in an EBIT and sympathetic cooling inside of a Coulomb crystal of laser-cooled Be + ions contained in a linear RF trap (Schwarz et al, 2012;Versolato et al, 2013) has demonstrated how to bring the temperature of HCI by 8 orders of magnitude down to the mK regime, and opened the possibilities afforded by RF traps to the study of HCI. An artist's impression and schematic are shown in Figure 9 and Figure 10, respectively.…”
Section: B Sympathetic Cooling Of Hcimentioning
confidence: 99%
“…Recently, a combination of HCI production in an EBIT and sympathetic cooling inside of a Coulomb crystal of laser-cooled Be + ions contained in a linear RF trap (Schwarz et al, 2012;Versolato et al, 2013) has demonstrated how to bring the temperature of HCI by 8 orders of magnitude down to the mK regime, and opened the possibilities afforded by RF traps to the study of HCI. An artist's impression and schematic are shown in Figure 9 and Figure 10, respectively.…”
Section: B Sympathetic Cooling Of Hcimentioning
confidence: 99%
“…Moreover, sympathetic cooling may be employed similar to the scheme used in Al + clock, which is cooled using lasercooled Be + or Mg + ions [1]. The experimental investigations toward the sympathetic cooling of HCIs and the precision laser spectroscopy of forbidden transitions are in progress [12][13][14][15]. A cooling scheme combining laser cooling of Be + ions and sympathetic cooling of Xe 44+ by Coulomb collisions with the cold Be + ions has been demonstrated in [16].…”
Section: Introductionmentioning
confidence: 99%
“…In most of the proposed HCIs with atomic number Z ¼ 55-98 and in charge states from 7 to 35, the complex electronic structures are experimentally unknown, and accurate calculations are extremely difficult. In view of novel techniques for sympathetically cooling HCIs in Paul traps [13][14][15] aiming at quantum logic spectroscopy on highly forbidden transitions [16], such data are urgently required.Observations from quasar absorption spectra have suggested a spatial variation of the value of the fine-structure constant α over cosmological dimensions [17], characterized by a dipolar distribution with a value of 10 −6 GLyr −1 . Laboratory experiments [18][19][20][21] have not yet reached the accuracy needed to test this dipolar pattern, which translates to a temporal variation of 10 −19 yr −1 [22] due to the motion of the Earth.…”
mentioning
confidence: 99%
“…In most of the proposed HCIs with atomic number Z ¼ 55-98 and in charge states from 7 to 35, the complex electronic structures are experimentally unknown, and accurate calculations are extremely difficult. In view of novel techniques for sympathetically cooling HCIs in Paul traps [13][14][15] aiming at quantum logic spectroscopy on highly forbidden transitions [16], such data are urgently required.…”
mentioning
confidence: 99%
See 1 more Smart Citation